KINERJA DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA DENPASAR DALAM MENGELOLA SAMPAH BESAR MELALUI PROGRAM PENANGANAN SAMPAH BESAR GRATIS DENPASAR (PESAN GADIS) - Arini, Lilin; Sastra Wijaya, Komang Adi; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2021)
DLHK has initiated an innovative program to tackle this problem where people can dispose of waste in a more safe manner. The program “Pesan Gadis” is a door-to-door large garbage collection service for the people of Denpasar city, and free of charge. The purpose of this study to determine the performance of the Denpasar City Environment and Hygiene Service in Managing Large Waste through “Pesan Gadis” program. The theory used is the Performance Theory from Dwiyanto, which contains five indicators, namely Productivity, Service Quality, Responsiveness, Responsibility, and Accountability. This research uses descriptive qualitative methods.The results showed that the performance of the Denpasar DLHK in Managing Large Waste through the “Pesan Gadis” program had been going well but not yet optimal due to the lack of facilities and infrastructure, an ineffective work task system, and socialization has not embraced the community so that the “Pesan Gadis” program looks passive.